Understanding the Connections between the EU Global Strategy and Somali Peacebuilding Education Needs and Priorities. Issue 4 (14th June 2018) - Lewis, Alexandra; Winn, Neil
Abstract: This paper examines the connections between identity politics and European Union (EU) aid effectiveness in peacebuilding education in Somalia. It engages with a severe educational challenge, which is that a lack of capacity in rigorous educational design and/or implementation across Somali Ministries in the South Central Zone, Somaliland and Puntland has led to the importation of multiple foreign curricula into the country simultaneously that do not address Somali history and contemporary conflict drivers and that frequently clash with local values as well as with each other. We critique this from a 'new barbarism' perspective, arguing that Somali voices and educational priorities have not been provided a sufficient space for expression in the EU debate on the global and therefore also the national development agenda. Abstract : In order to promote genuine societal transformation, we need to be moving away from peace education delivery that aims to make people less violent or less Barbarian, towards peacebuilding education that aims to question the critical role of education in society in order to overcome social injustice.